Evaluation of the effect of local administration of PRP vs vitamin D3 on the rate of orthodontic tooth movement and the associated external apical root resorption - S. Navya; G.S. Prashantha; S. Sabrish; M.S. Roshan; S. Mathew (Elsevier, 2022)
Background: Increased orthodontic treatment duration is associated with iatrogenic risks such as root resorption, white spot lesions etc. Recent research using pharmacological agents to accelerate tooth movement has mostly been conducted on animals and there is no reported research conducted on humans comparing the effects of Vitamin D3 and Platelet Rich Plasma (PRP) in the same subjects using a split mouth technique. Objectives: To determine and compare effects of local injection of PRP and Vitamin D3 on the rate of tooth movement. Also, to assess association of external apical root resorption with the use of PRP, Vitamin D3 and compare it to a control group. Materials & methods: 11 subjects who diagnosed with Class I bi-maxillary malocclusion and who gave informed consent were recruited in the study. The patients were randomly divided using split mouth design and each quadrant served as either experimental or control group one. At the beginning of retraction phase, Vitamin D3 and PRP were injected to the randomly assigned quadrants while the contralateral side served as a control. The amount of space closure in 4 months was measured from distal surface of canine to mesial surface of 2nd premolar. Root resorption was assessed using CBCT taken at the beginning and at the closure of retraction phase. Results: Mean rate of tooth movement was higher in PRP and Vitamin D3 groups compared to their controls. In the PRP group, the increased rate of tooth movement was observed throughout the study interval, but in the Vitamin D3 group it was only seen in first two months. Also, the PRP group demonstrated a higher rate of tooth movement compared to Vitamin D3 group. Root resorption was lesser in both experimental groups. Among the teeth assessed, lateral incisor showed maximum root resorption and canine the least. Conclusions: PRP is a more efficient pharmacological agent compared to Vitamin D3 for accelerating tooth movement.